Emojis og ikke-standard stavemåder i gruppechats - Jensen, Monica Aznar; Bruun, Samuel Bartholdy (Journal of Language Works - Sprogvidenskabeligt Studentertidsskrift, 2025)
This study examines the use of emojis and non-standard orthography in digitally mediated interactions (DMI) in Danish group chats. We investigate the interactional functions of three categories of language use in DMI: the use of emojis and emoticons, repeated letters, and written laughter. In this, we consider the normative standards within the groups and how they inform which linguistic strategies are used. Data from this study consists of private messages written in three different group chats and is supplemented with data from semi-structured interviews with the group chat members. In this article, we present a new, syntactic use of emojis and discuss the meaning conveyed by the use of emojis compared to that of emoticons. We also show how a specific group of emojis in DMI can be used as contextualisation cues with weakened semantic properties. We argue that non-standard orthography has acquired an additional use in the form of contextualisation cues in contexts not related to emulation of speech, as seen in the use of letter repetition as a discourse softener and the distinct functions of different variations of written laughter.